KOMUNIKASI BERDAKWAH - Muhammad Amin Sihabuddin (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
Based on the results of the study, it is understood that da'i ethics which are regulated in the al-Qur'an are grouped into three categories, namely speaking ethics. Da'i in preaching oral bil al according to the norms of the Koran must be in clear language (baligh), not burdensome to the audience, polite language (qaulan layyinah), language ethics according to the forum, and the principle of amar ma'ruf nahi munkar ; (2) Deed ethics, is the regulation of the norms of the Koran regarding the deeds of preachers, namely to do good in accordance with the words, to be affectionate to the public, istiqamah, to manifest faith with righteous deeds, to do good deeds in accordance with Islamic law, to leave Allah's prohibition and carrying out orders, not being harsh to the public and compelling, and (3) ethics in exemplary, namely as a profile of the manifestation of good values (mahampang) according to the norms of the Koran that exemplary da'i, is a moral manifestation of al-Qur'an with its polite appearance, close relationship with the people, spreading the form of love as a preacher with mad'u, and totally surrendering to the truth value of the Koran.